2023
DOI: 10.1021/acs.bioconjchem.3c00156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Excision Repair of Site-Specific 3′-End DNA-Histone Cross-Links Derived from Abasic Sites

Abstract: Histones catalyze the DNA strand incision at apurinic/apyrimidinic (AP) sites accompanied by formation of reversible but long-lived DNA−protein cross-links (DPCs) at 3′-DNA termini within single-strand breaks. These DPCs need to be removed because 3′-hydroxyl is required for gap-filling DNA repair synthesis but are challenging to study because of their reversible nature. Here we report a chemical approach to synthesize stable and site-specific 3′-histone-DPCs and their repair by three nucleases, human AP endon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The traditional sample preparation involves a sequential DPC digestion by a protease (e.g., trypsin) and a nuclease cocktail . A limitation is that the steric hindrance imposed by the cross-linked peptide can inhibit DNA digestion, resulting in a heterogeneous mixture of modified peptides that are not suitable for mass spectrometry analysis. , We recently developed an LC-MS/MS workflow to characterize 3′-DPCs formed through Michael addition by using a 3′-DPC repair enzyme, tyrosyl-DNA phosphodiesterase 1 (TDP1), as a molecular tool to specifically release tryptic 3′-DPCs to yield homogeneous samples. In this study, we developed a similar LC-MS/MS pipeline to detect Schiff base 3′-histone-DPCs. Our method (Figure B) involves four major steps: (1) stabilizing 3′-histone-DPCs by NaBH 4 reduction, (2) excising intact histones by excess TDP1, (3) acylating modified histones by propionic anhydride before and after trypsin digestion to improve the separation of histone peptides on HPLC, and (4) LC-MS/MS analysis and identification of histone peptides that contain a dynamic modification of K + 100.0524 Da.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional sample preparation involves a sequential DPC digestion by a protease (e.g., trypsin) and a nuclease cocktail . A limitation is that the steric hindrance imposed by the cross-linked peptide can inhibit DNA digestion, resulting in a heterogeneous mixture of modified peptides that are not suitable for mass spectrometry analysis. , We recently developed an LC-MS/MS workflow to characterize 3′-DPCs formed through Michael addition by using a 3′-DPC repair enzyme, tyrosyl-DNA phosphodiesterase 1 (TDP1), as a molecular tool to specifically release tryptic 3′-DPCs to yield homogeneous samples. In this study, we developed a similar LC-MS/MS pipeline to detect Schiff base 3′-histone-DPCs. Our method (Figure B) involves four major steps: (1) stabilizing 3′-histone-DPCs by NaBH 4 reduction, (2) excising intact histones by excess TDP1, (3) acylating modified histones by propionic anhydride before and after trypsin digestion to improve the separation of histone peptides on HPLC, and (4) LC-MS/MS analysis and identification of histone peptides that contain a dynamic modification of K + 100.0524 Da.…”
mentioning
confidence: 99%
“…Unrepaired 3′-histone-DPCs are extremely toxic, as they will block DNA replication and transcription. We recently demonstrated that 3′-histone-DPCs can be efficiently repaired by three nucleases including TDP1, AP endonuclease 1, and three-prime repair exonuclease 1, but only when the cross-linked histones are initially digested by trypsin . How 3′-histone-DPCs are degraded in cells warrants future investigation.…”
mentioning
confidence: 99%
“…We determined the alkylation sites based on the fact that alkylated adducts were usually heat susceptible under alkaline conditions, leading to strand breaks at alkylation sites. 29,30 It was found that A5, G6, A14, A15, A18, G22, C23, A24, A25, and G27 were the major cleavage sites. Meanwhile cleavage was also found at C3, C9, and C19 for 15 treated with 14 (Fig.…”
mentioning
confidence: 99%